Thio(seleno)cyano-difluoroalkylation of Alkenes Using Visible-Light Photocatalysis - Choi, Ye Rin; Lee, Seok Beom; Lee, Jae Kyun; Kwak, Yoonna; An, Hongchan; Choi, Sungwook; Hong, Ki Bum (American Chemical Society, 2023)
A mild and efficient three-component thio(seleno)cyano-difluoroalkylation of simple alkenes is demonstrated using an iridium(ruthenium) photocatalyst. This protocol provides a direct and regioselective installation of both C-S(Se)CN [thio(seleno)cyanation] and C-CF (difluoroalkylation) bonds.